Park Avenue summer - Rosen, Renée (New York : Berkley, 2019)
It's 1965 in New York City and Helen Gurley Brown, the new editor-in-chief of Cosmopolitan, shocks America and saves a dying publication by daring to talk to women about everything off-limits. Alice Weiss is a single girl from a small midwestern town who unexpectedly lands a job at Cosmo, a job nothing could have prepared her for. When someone tries to pull Alice into a scene to sabotage her boss, she is more determined than ever to help Helen succeed. As pressure mounts and Alice struggles to make her way in New York, she quickly learns that in Helen's world, a woman can demand to have it all.
"Readers guide included"--Page 4 of cover.
Keywords: Brown, Helen Gurley -- Fiction; Young women -- New York (State) -- New York -- Fiction; Female friendship -- Fiction; New York (N.Y.) -- Fiction; Historical fiction